Marketing Strategy of Non-Steroidal Anti Inflammatory (NSAIDs) Selective Cox-2 Inhibitor To Increase Demand By Sales Driven Of Pharmacist’s Recommendation Based On Aisas Model In The Retail Pharmacy - Utomo Go, Cahayadi (Politeknik Siber Cerdika Internasional, 2024)
Inflammation is a condition that generally occurs in patients with joint-related diseases or injuries that are characterized by pain. In treating pain, the drugs often used are NSAIDs, especially COX-2, which have advantages for patients with Gastrointestinal (GI) problems and are relatively safe for patients with a Cardiovascular (CV) disease history. In the retail pharmacy, the Sanisphere data shows that 33% of pharmacy transaction sales volume is driven by recommendations from pharmacists and frontline employees. Pharmaceutical companies have a significant opportunity to increase demand through pharmacist recommendations in the retail segment, especially for NSAIDs COX-2. This research focuses on implementing an effective marketing strategy using the AISAS Model. Qualitative and Quantitative methods use open and closed-question surveys to analyze the perspective of pharmacists and frontliners regarding influencing factors and marketing activities and tools effectively implemented in the retail pharmacy segment. Competitors, marketing mix, Segmentation, targeting, and positioning have also been analyzed in this research. The research results show that pharmacists consider the following factors for COX-2: Drug indications and pain symptoms, Drug Safety, Drug risk, Drug quality, strength, Onset and effectiveness in treating pain, product knowledge, marketing activities, patient economics, and patient’s request on drug molecule. Several practical marketing activities are applied at each stage of the AISAS Model, Detailing product knowledge, merchandise, discounts, seminars, webinars, marketing activities, sponsorships, and sales visiting activities. Pharmaceutical companies can implement this effective marketing activity proposal to increase demand for COX-2 NSAIDs in pharmacies through pharmacist and frontline recommendations